Carotenoid Signaling and Mitochondrial Protection at the Crossroads of Cardio-Oncology: Lycopene as a Dual Modulator of Cardiovascular and Cancer Risk - Barack Ndenga (Publisher, 2025)
I explore the role of lycopene, a non-provitamin A carotenoid predominantly derived from tomatoes, as a dual biological modulator at the interface of cardiovascular disease and cancer. Cardio-oncology has highlighted the shared pathophysiological mechanisms underlying these two leading causes of mortality, particularly mitochondrial dysfunction, oxidative stress, and chronic inflammation. Beyond its well-established antioxidant capacity, lycopene exerts regulatory effects on intracellular signaling pathways involved in mitochondrial homeostasis, apoptosis, lipid metabolism, and redox balance. In this review, I synthesize mechanistic, experimental, and clinical evidence supporting lycopene-mediated carotenoid signaling and mitochondrial protection as convergent mechanisms contributing to both cardiovascular and oncological risk reduction. I further discuss translational implications, limitations of current evidence, and future research directions within the evolving field of cardio-oncology. Keywords : Lycopene; Cardio-Oncology; Mitochondrial Dysfunction; Carotenoid Signaling; Cardiovascular Disease; Cancer Prevention
This work explores the role of lycopene, a tomato-derived carotenoid, as a dual biological modulator at the intersection of cardiovascular disease and cancer within the emerging field of cardio-oncology. Focusing on carotenoid signaling and mitochondrial protection, the manuscript examines how lycopene influences redox homeostasis, inflammation, mitochondrial integrity, and apoptotic regulation—mechanisms shared by both cardiovascular and oncologicalpathologies. By integrating mechanistic insights with translational perspectives, this work highlights the potential of lycopene as a low-risk, nutrition-based strategy for reducing cardiometabolic and cancer-related risk. The study emphasizes mitochondria as a unifying biological target and contributes to the growing discourse on precision nutrition and preventive approaches in cardio-oncology.